THE RELATIONSHIP BETWEEN THE READING HABIT AND SPELLING ABILITY OF THE STUDENTS AT SMPN 49 MAKASSAR - Uhrawi, Teti; Talib, Ahmad; G, Hasriani (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This research intends to determine the relationship between reading habits and the spelling ability of students. The research population for this research was eighth-grade students at SMPN 49 Makassar University. The researcher applied a random cluster sampling technique and chose randomly class VIII3 which consist of 32 students. The correlation design was used in the research. Data were collected using two instruments: a questionnaire to obtain the reading habits of the students was the first instrument. The second instrument was a test to obtain students’ spelling ability. The research findings showed that the average student's reading habit was in the low category. The same result for spelling ability, the students are in the low category. This can be observed from the average questionnaire result of 51 and the average test result of 38.59. In addition, the Pearson product-moment correlation result was 0.783. This denotes that the degree of the relationship coefficient () exceeded the degree shown in the R table. In this particular circumstance, , because the r value in the r table is positive, implying that the relation between the two variables is positive. In sum, the better the students' reading habits, the better the students' spelling ability. Besides, there is a two-tailed Sig. of 0.000 < 0.05, which implies that spelling ability and reading habit are significantly correlated. This implies that H0 is dismissed and H1 is acceptable. Therefore, the reading habit and spelling ability in SMPN 49 Makassar are significantly correlated.